An integrated biorefinery process for co-production of xylose and glucose using maleic acid as efficient catalyst. (April 2021) - Liu, Zhenghui; Shi, Enze; Ma, Feng; Jiang, Kankan
Highlights: Wheat straw was treated by maleic acid for xylose recovery and enzymatic hydrolysis. High xylose recovery and enzymatic hydrolysis was achieved under optimal conditions. Maleic acid was an efficient pretreatment acid with low amount of furfural produced. Abstract: This study aims to valorize wheat straw for xylose and glucose recovery using maleic acid in the pretreatment. The process conditions of maleic acid hydrolysis of wheat straw for xylose recovery were optimized by response surface methodology, through which the maximum xylose recovery of 77.12% versus minimum furfural yield of 1.61% were achieved using 70 g/L solid-to-liquid ratio and 0.1 mol/L maleic acid for 40 min at 150 °C. Moreover, 88.58% cellulose conversion was achieved by enzymatic hydrolysis of maleic acid-pretreated wheat straw. Results showed that maleic acid was an effective pretreatment solvent for sugars recovery: 19.88 g xylose and 30.89 g glucose were respectively obtained from 100 g wheat straw due to acidic and enzymatic hydrolysis, with only 0.37 g furfural produced. This study provides a strategy for hydrolyzing wheat straw to produce fermentable sugars with low amount of degradation product.